A Change in Directions and Consumers’ Demand during COVID-19 Pandemic with Future Business Trends in People’s Republic of China - Khonkhlong, Suppakorn (Business Administration and Management Journal Review, 2023)
Since the beginning of 2020 onwards, there has been a severe spread of the COVID-19 virus in the People’s Republic of China, and there are numerous of emergencies announcement and defensive measure that affected people cannot live their normal life. This situation has led to a state of stagnation in society. Altogether these states causing damage to the business sector, there are countless businesses being standstill till shutting down. Moreover, amid the crisis that consumers are unable to move as they wish, this has made some businesses grow in leaps and bounds, such as online learning, online entertainment, online shopping. This indicates that during the COVID-19 situation, consumers have changed their behavior from buying products or using the storefront services to the internet more and more. It shows that even in crisis, but there is still a chance. Learning and understanding what is happening in the People’s Republic of China will be a key to helping businesses for seeking the opportunity to survive during the outbreak of the COVID-19 and to respond to the needs of consumers in the Stay at Home Economy.